Multicultural Learning Competence Analysis of Teachers in Madrasah Ibtidaiyah - Sulistiono, Muhammad; Mansur, Rosichin (Universitas Nahdlatul Ulama Blitar, 2024)
Madrasah Ibtidaiyah Negeri I Malang shows a multicultural level in educational values. Therefore, the purpose of this research is to find out the pattern of teacher multicultural learning competencies in managing diversity from various backgrounds among the residents of MIN 1 Malang. This research used a qualitative approach to phenomenological research. Research findings and results: 1) multicultural experiences of teachers include; perception alerts, problem solving, and surveys. 2) The teacher's knowledge of the cultural background of students includes; knowledge of multicultural values and cultural knowledge of students. 3) teacher skills in multicultural-based learning include; transparent norms and expectations, awareness of change, and productive interaction. The conclusions in this study show that the competence of teachers at Madrasah Ibtidaiyah Negeri I Malang City in general has multicultural competence with interesting and unique patterns.